Dysregulation of mitochondrial bioenergetics and quality control by HIV‐1 Tat in cardiomyocytes. Issue 2 (31st July 2017) - Tahrir, Farzaneh G.; Shanmughapriya, Santhanam; Ahooyi, Taha Mohseni; Knezevic, Tijana; Gupta, Manish K.; Kontos, Christopher D.; McClung, Joseph M.; Madesh, Muniswamy; Gordon, Jennifer; Feldman, Arthur M.; Cheung, Joseph Y.; Khalili, Kamel
Abstract : Cardiovascular disease remains a leading cause of morbidity and mortality in HIV‐positive patients, even in those whose viral loads are well controlled with antiretroviral therapy. However, the underlying molecular events responsible for the development of cardiac disease in the setting of HIV remain unknown. The HIV‐encoded Tat protein plays a critical role in the activation of HIV gene expression and profoundly impacts homeostasis in both HIV‐infected cells and uninfected cells that have taken up released Tat via a bystander effect. Since cardiomyocyte function, including excitation‐contraction coupling, greatly depends on energy provided by the mitochondria, in this study, we performed a series of experiments to assess the impact of Tat on mitochondrial function and bioenergetics pathways in a primary cell culture model derived from neonatal rat ventricular cardiomyocytes (NRVCs). Our results show that the presence of Tat in cardiomyocytes is accompanied by a decrease in oxidative phosphorylation, a decline in the levels of ATP, and an accumulation of reactive oxygen species (ROS). Tat impairs the uptake of mitochondrial Ca 2+ ([Ca 2+ ]m ) and the electrophysiological activity of cardiomyocytes. Tat also affects the protein clearance pathway and autophagy in cardiomyocytes under stress due to hypoxia‐reoxygenation conditions. A reduction in the level of ubiquitin along with dysregulated degradation of autophagy proteins including SQSTM1/p62 and a reduction of LC3 II were detected in cardiomyocytes harboring Tat. These results suggest that, by targeting mitochondria and protein quality control, Tat significantly impacts bioenergetics and autophagy resulting in dysregulation of cardiomyocyte health and homeostasis. Abstract : Tat expression increases mitochondrial mass and impairs mitophagy. ICC using an antibody againse Tom20 showed that Tat altered mitochondrial morphology.